2013
DOI: 10.4161/cc.23513
|View full text |Cite
|
Sign up to set email alerts
|

A knockout screen for protein kinases required for the proper meiotic segregation of chromosomes in the fission yeast Schizosaccharomyces pombe

Abstract: The reduction of chromosome number during meiosis is achieved by two successive rounds of chromosome segregation after just single round of DNA replication. To identify novel proteins required for the proper segregation of chromosomes during meiosis, we analyzed the consequences of deleting Schizosaccharomyces pombe genes predicted to encode protein kinases that are not essential for cell viability. We show that Mph1, a member of the Mps1 family of spindle assembly checkpoint kinases, is required to prevent me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 74 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…The eponymous DBF4 protein is an activator of the CDC7 serine/threonine kinase, which has a conserved role in DNA replication initiation from yeast to humans (Hughes et al 2012). In yeast, the dbf4/cdc7 complex was moreover linked to chromosome segregation during meiosis (Kovacikova et al 2013;Le et al 2013). Coincidently, we found that Liz expression peaks at meiosis during mouse spermatogenesis, and canonical Zdbf2 is highly transcribed in the oocyte, leading to the exciting possibility that Zdbf2 may fulfill meiotic roles in mammals.…”
Section: Discussionmentioning
confidence: 61%
“…The eponymous DBF4 protein is an activator of the CDC7 serine/threonine kinase, which has a conserved role in DNA replication initiation from yeast to humans (Hughes et al 2012). In yeast, the dbf4/cdc7 complex was moreover linked to chromosome segregation during meiosis (Kovacikova et al 2013;Le et al 2013). Coincidently, we found that Liz expression peaks at meiosis during mouse spermatogenesis, and canonical Zdbf2 is highly transcribed in the oocyte, leading to the exciting possibility that Zdbf2 may fulfill meiotic roles in mammals.…”
Section: Discussionmentioning
confidence: 61%
“…Spindles for meiosis II are often fragmented in these mutants [14]. In contrast, another recent report showed that abnormally elongated anaphase II spindles frequently overlap and thus destroy the linear order of nuclei in the ascus in the absence of Spo4 or Spo6 [45]. Thus Spo4-Spo6 may have a critical function in regulating the spindle length during meiosis II.…”
Section: Regulation Of Meiotic Cell Division By Hsk1/cdc7 and Relatedmentioning
confidence: 80%
“…Spo4 and its regulator Spo6 are expressed exclusively in meiosis, and while Spo4 is dispensable for meiotic replication, it contributes to meiotic chromosome segregation [69]. Consistent with this, its absence only affects late events and results in abnormally elongated anaphase II spindles that abolish the linear order of nuclei in the ascus [70]. These observations suggest that higher levels of DDK and related kinase activities are important for the execution of meiotic recombination and chromosome segregation.…”
Section: A Quantitative Model For Cyclin-dependent Kinase and Dbf4mentioning
confidence: 95%